If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4q + -34 = 2q Reorder the terms: -34 + 4q = 2q Solving -34 + 4q = 2q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-2q' to each side of the equation. -34 + 4q + -2q = 2q + -2q Combine like terms: 4q + -2q = 2q -34 + 2q = 2q + -2q Combine like terms: 2q + -2q = 0 -34 + 2q = 0 Add '34' to each side of the equation. -34 + 34 + 2q = 0 + 34 Combine like terms: -34 + 34 = 0 0 + 2q = 0 + 34 2q = 0 + 34 Combine like terms: 0 + 34 = 34 2q = 34 Divide each side by '2'. q = 17 Simplifying q = 17
| 3x+15=1x+21 | | 40c^2/8c | | z(z+1)=11+3i | | 7+2z=13 | | 4q-34=29 | | -12x^2+12=156x | | 6p+27=9p | | ax^2+12x+9=0 | | −5=f/5 | | z(z-1)(z+3)=11+3i | | 3ax^2+2ax-1=0 | | (4x-6)/5=90 | | 8-(4n-8)=-8 | | 2(x-1)=3x-7 | | 25-2x=15 | | 1.8x-8=22 | | 2x-(-4)=96+(-10) | | 3x+4y=9.4 | | 4z/6-6=5 | | d/12-6=1 | | -8x+2=74 | | 6=-3+v | | -18a/6 | | 3x+4x=9.4 | | f(x)=3x^4-13x^2+14 | | 1.8q-5.4-1.7q=-0.9q-5.1 | | 2(5c-5.1)=-20.1 | | 128=-t^2+6t | | 22+7=3(22)-3 | | 2(x+3)=x+5+x | | 2(3x+1)=10x-6 | | Rx+sy=16 |